Does the primate pattern hold up? Testing the functional significance of infraorbital foramen size variation among marsupials. Issue 1 (25th January 2016) - Spriggs, Amanda N.; Muchlinski, Magdalena N.; Gordon, Adam D.
ABSTRACT: Objectives: The relative size of the infraorbital foramen (IOF) has been used to infer the ecology of extinct primates for several decades. Primates have relatively smaller IOFs than most other mammals, which may result from the fact that they pre‐process and manipulate food with their hands rather than their muzzles. In primates, relative IOF area co‐varies with diet, where insectivores and folivores have relatively smaller IOFs than frugivores. We wanted to determine whether the observed patterns associated with IOF variation hold across other orders. Materials and Methods: We examined how relative IOF area differs among marsupials occupying different ecological niches. Marsupials were chosen because they converge with primates in both ecology and morphology, but unlike primates, some marsupials approach and pre‐process foods only with their muzzles. We measured IOF area and cranial lengths from 72 marsupial species, and behavioral feeding data were obtained from a subset of this sample ( N = 20). Results: Relative IOF area did not vary significantly between substrate preferences. However, relative IOF area differed significantly by diet category ( P < 0.001). Species that specialize in feeding on non‐grassy leaves have significantly smaller relative IOF areas than species which primarily feed on grasses, insects, vertebrates, or some combination thereof. Behavioral analyses support that folivorous marsupials approach and remove food with the hands more often than marsupials from other dietary groups. Discussion: Results suggest that relatively small IOF area may reflect increased reliance on the hands while feeding, and that relative IOF size can be used as an indicator of feeding behavior. Am J Phys Anthropol 160:30–40, 2016. © 2016 Wiley Periodicals, Inc.